More for less security operations centers--improving resiliency while simultaneously reducing cost - Bellwether Group; Safari eBooks (Upper Saddle River, NJ : FT Press Delivers, 2012)
"Today, businesses can monitor security and operations at all facilities within an integrated infrastructure of Global Security Operations Centers (GSOCs)-thereby responding more quickly, effectively, and cost-efficiently to any actual or potential breach or disruptive event. Now, The Bellwether Group fills the gap on public literature on this subject, showing business and IT decision-makers how to use new GSOC techniques and technologies to increase operational resiliency in the face of security, safety, and other disruptive events, while at the same time reducing staffing and system-wide costs. Bellwether's expert consultants explain how to implement a small number of physical GSOCs in different time zones to create a truly global infrastructure capable of supporting each other in emergencies. They demonstrate how to build efficient 'virtual' GSOC infrastructures based on common, web-enabled platforms; accommodate activity peaks and long-term growth; centrally collect incident and event information for real-time analysis; and drive even more value by extending GSOCs into facilities management and supply chain security. GSOCs are becoming an increasingly widespread 'best practice' among investment banks, asset management firms, manufacturers, retailers, and in other industries. This document draws on the experiences of these leading-edge implementers to offer insights of significant value to every large and mid-sized company."--Resource description page.
Cover title.
"Digital shorts."
Keywords: Business enterprises -- Security measures; Industrial management; Crisis management; Emergency management; Electronic books